PENGEMBANGAN BAHAN AJAR E-BOOK BERBASIS BOOK CREATOR PADA TOPIK BANGUN DATAR KELAS IV - Siti Luthfiyyah Salsabila; Lina Novita; Nur Hikmah (STKIP Subang, 2026)
Siti Luthfiyyah Salsabila 037121099. Development of E-Book Teaching Materials Based on Book Creator on the Topic of Flat Shapes for Grade IV.This research aims to produce a product in the form of e-book teaching materials based on Book Creator on the topic of flat shapes for Class IV-A at SDN Ciomas 06, involving 28 students. The product development follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research began with needs analysis, curriculum analysis, student analysis, and product design. The researcher then developed the e-book teaching materials, conducted expert validation, and carried out a limited trial of the e-book teaching materials based on Book Creator with selected respondents. The validation results from media experts, language experts, and material experts indicated that the e-book teaching materials based on Book Creator are highly valid and very feasible for use, with an average percentage score of 96.07%. During the trial phase involving 28 students, the teaching materials received very good and highly engaging responses, with an average percentage score of 88%. Based on the research results, it can be concluded that the e-book teaching materials based on Book Creator on the topic of flat shapes developed in this study are proven to be feasible, easy to use, and engaging for students.